2022-LBA-718-ESGO Sentinel node biopsy for endometrial cancer by retroperitoneal transvaginal natural orifice transluminal endoscopic surgery. (27th October 2022) - Huber, Daniela; Hurni, Yannick
Abstract : Introduction: Surgical staging with sentinel lymph node biopsy (SLNB) is an important tool to guide the management of early-stage endometrial cancer. This staging is generally performed by minimally invasive techniques such as conventional, single-site, or robotic laparoscopy. To further reduce the morbidity related to transabdominal surgeries, SLNB by total retroperitoneal transvaginal natural orifice transluminal endoscopic surgery (vNOTES) was recently introduced at our institution. Here, we describe how to perform this surgical technique and we report our preliminary results. Methods: Indocyanine green was injected into the cervix to identify sentinel lymph nodes (SLNs). Access to the pelvic retroperitoneal space was achieved through a paracervical incision in the lateral vaginal fornix, providing access to the obturator fossa. A 7 cm GelPoint transvaginal access platform was used as a vNOTES port, and CO2 was insufflated to expand the retroperitoneal space. SLNs were identified using fluorescence imaging, carefully resected, and removed transvaginally. Results: Eleven patients underwent SLNB by vNOTES at our institution between October 2021 and July 2022. Indications to perform SLNB were endometrial cancer (8 cases) and endometrial complex atypical hyperplasia (3 cases). The median operative time was 113 (81–211) minutes. The median estimated blood loss was 20 (20–400) mL. The overall bilateral detection rate was 100% (10/10). We completed all procedures without significant intraoperative complications, but 1 case required conversion to conventional laparoscopy. The median postoperative stay was 2 (2–4) days. We observed one case of postoperative deep vein thrombosis and an asymptomatic vaginal vault hematoma in one patient and a retroperitoneal hematoma requiring surgical drainage in another. Definitive results are not available at the time of abstract submission and will be updated later. Conclusions: Our preliminary experience suggests that retroperitoneal vNOTES is a safe, feasible, and valuable technique to perform SLNB in gynecological malignancies.